A cross-sectional analysis on the association between pain and making tradeoffs for survival using a multidimensional health assessment tool among older adults living in low-to middle-income areas in Cape Town, South Africa - Steyn, Simone (Department of Public Health and Family Medicine, 2022)
Introduction Globally, the population of older adults is ageing rapidly, due to increased longevity and decreasing fertility rates. With the rapidly accelerating growth of this ageing population in low-to-middle income countries, the health systems are not well resourced to manage this rapid growth that are required to accommodate older multimorbid populations. Multimorbidity presents as an elevated risk for the health and wellbeing of older populations and occurs when more than one chronic condition is present. Globally pain is a common symptom among older adults that impairs health with severe consequences especially when multimorbidity is present. Some evidence has shown that living under poverty-stricken conditions is associated with increased pain, particularly among vulnerable populations such as older adults. There is limited evidence in Cape Town on the relationship between living in low-to middle income areas and poverty indicators such as making financial trade-offs for survival with increased reports of pain in older adults. Methods In this cross-sectional analysis, adults aged 60 years and above seeking care from four selected primary health care clinics and health clubs were enrolled in an ongoing longitudinal study (Wellbeing Study). Data was used from an existing study that commenced in March 2018. Data were collected using a multidimensional geriatric instrument called the Check-Up Self-Report (interRAI). The researcher assessed the relationship between financial trade-offs made for survival (as a proxy for poverty) and pain in the last three days (as a proxy for pain) overall, and according to study sites. Permission for the parent study was sought and granted by the University of Cape Town's Health Research Ethics Committee (UCT-HREC, Ref: 790/2017) as well as by the Western Cape Department of Health. Results The results highlighted that overall and by site, no associations were observed between pain and financial trade-offs after adjusting for various health-related variables (aOR: 1.17, 95% CI: 0.97 – 1.42). Of the 1813 older adults included in this analysis (64% female, median age 68 years (IQR: 64-74)) 51% reported making financial trade-offs and 46% reported experiencing pain in the last three days. Overall, a moderate proportion of participants (27%) reported daily pain, which was categorised as not severe (11%), severe (12%) and excruciating (4%). When assessed by site a significantly higher proportion of participants reported daily pain in Khayelitsha (43%) and Woodstock (40%). Conclusion In this study the need to make financial trade-offs for survival and pain were prevalent in this population. Although an association was not found between making financial trade-offs and recent pain, the results provided valuable information that can drive future research studies and policy. The use of this multidimensional tool which collects information from various health categories and provides broad and less in-depth data may have played a role in the nullified results. Further research is needed to evaluate the association of poverty indicators on pain in this population using more detailed pain and poverty assessment tools.